Getting caught up in the game: managing non-formal dynamics in the remediation of contaminated sediments in Oslo harbor. Issue 5 (3rd May 2016) - Duijn, Michael; van Buuren, Arwin; Sparrevik, Magnus; Slob, Adriaan; Ellen, Gerald Jan; Oen, Amy
Abstract : This study aims at describing, analyzing and evaluating the relation between management styles and process dynamics of a complex planning process confronted with unexpected dynamics. The development of an aquatic disposal site for dredged contaminated sediments in Oslo was managed by a project management style focused on timely and cost-effective implementation. Coupling the remediation project with another infrastructural project and the actual construction of the site led to unexpected dynamics in terms of resistance and controversy. Project management had difficulties in adjusting its style accordingly, resulting in even more delay and resistance. Managing complex planning projects requires a style suitable to the characteristics of the project and the capability of adjusting it to changing circumstances. The paper concludes with some explanations why it is difficult to change management styles in complex planning and implementation processes and complexity-embracing approaches to deal with this.